A three-dimensional tissue-engineered rostral migratory stream as an in vitro platform for subventricular zone-derived cell migration - Purvis, Erin M.; Garcia-Epelboim, Andrés D.; Krizman, Elizabeth N.; O’Donnell, John C.; Cullen, D. Kacy (Frontiers in Bioengineering and Biotechnology, 2024)
In the brains of most adult mammals, neural precursor cells (NPCs) from the subventricular zone (SVZ) migrate through the rostral migratory stream (RMS) to replace olfactory bulb interneurons. Following brain injury, published studies have shown that NPCs can divert from the SVZ-RMS-OB route and migrate toward injured brain regions, but the quantity of arriving cells, the lack of survival and terminal differentiation of neuroblasts into neurons, and their limited capacity to re-connect into circuitry is insufficient to promote functional recovery in the absence of therapeutic intervention. Our lab has fabricated a biomimetic tissue-engineered rostral migratory stream (TE-RMS) that replicates some notable structural and functional components of the endogenous rat RMS. Based on the design attributes for the TE-RMS platform, it may serve as a regenerative medicine strategy to facilitate sustained neuronal replacement into an injured brain region or an in vitro tool to investigate cell-cell communication and neuroblast migration. Previous work has demonstrated that the TE-RMS replicates the basic structure, unique nuclear shape, cytoskeletal arrangement, and surface protein expression of the endogenous rat RMS. Here, we developed an enhanced TE-RMS fabrication method in hydrogel microchannels that allowed more robust and high-throughput TE-RMS assembly. We report unique astrocyte behavior, including astrocyte bundling into the TE-RMS, the presence of multiple TE-RMS bundles, and observations of discontinuities in TE-RMS bundles, when microtissues are fabricated in agarose microchannels containing different critical curved or straight geometric features. We also demonstrate that we can harvest NPCs from the SVZ of adult rat brains and that EGFP+ cells migrate in chain formation from SVZ neurospheres through the TE-RMS in vitro. Overall, the TE-RMS can be utilized as an in vitro platform to investigate the pivotal cell-cell signaling mechanisms underlying the synergy of molecular cues involved in immature neuronal migration and differentiation.